The correlational study of the frequency of listening English songs using YouTube and speaking performance of non-English Departments students at University of Islam Malang - Lisa Amelia (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: YouTube has become a popular digital media platform used by everyone. Most important to new knowledge, especially speaking skills students have effort and high creativity. In other contexts, students use YouTube for the frequency of listening to English songs to improve their English skills. A student using YouTube has effectively and better learning speaking skills. Moreover, the COVID-19 virus that has occurred in recent years has affected various educations.The main focus of this study is to know the correlational study of the frequency of listening to English songs using YouTube and speaking skills, to evaluate the application YouTube that they mostly use to listening English songs and speaking skills. In this study, some of the participants there were 30 the 6th-semester students majoring in Indonesian Language Education Departments of the University of Islam Malang became the subject of researchers with qualitative descriptive research methods. The main focus of this study is to know the correlational study of the frequency of listening to English songs using YouTube and speaking skills, to evaluate the application YouTube that they mostly use to listen to English songs and speaking skills. This study used descriptive qualitative research methods. Research conducted questionnaires to obtain information through qualitative descriptive research methods to collect more accurate and relevant information for use in interviews and surveys, while to get more specific and relevant information according to the questionnaire researchers use interviews. Researchers collected quiz data by using Google forms personal messages via WhatsApp to students of the Islamic University of Malang who had been the subject of this study. Furthermore, the researcher focused on conducting interviews using the Zoom application to obtain more significant information about the subject. The findings show that non-English students of the Islamic University of Malang during the pandemic, most students use YouTube to increase general knowledge in general, and broadly understand information related to English, especially by listening to English songs through YouTube. Overall, the statements from the participants suggested that they also benefited from uploading videos to YouTube, which allowed them to showcase their abilities by performing English songs and reading poetry. Utilizing the platform, the participants passionately upload YouTube videos. Some students used the web application YouTube to study English although this year's lessons were conducted entirely online. Meanwhile, even several university students actively utilize YouTube for enjoyment or other objectives.Data shows that most students have a YouTube account to be able to access information and improve the learning process according to the sources they want to know. From the data that has been collected by researchers, it can be concluded that using YouTube plays an important role in providing useful educational innovations for non-English students to understand by listening to English songs and speaking performances. Keywords: YouTube, Speaking Performance, Frequency Listening English songs